2009
DOI: 10.1007/s11745-009-3306-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Coconut Oil on the Biochemical and Anthropometric Profiles of Women Presenting Abdominal Obesity

Abstract: The effects of dietary supplementation with coconut oil on the biochemical and anthropometric profiles of women presenting waist circumferences (WC) >88 cm (abdominal obesity) were investigated. The randomised, double-blind, clinical trial involved 40 women aged 20-40 years. Groups received daily dietary supplements comprising 30 mL of either soy bean oil (group S; n = 20) or coconut oil (group C; n = 20) over a 12-week period, during which all subjects were instructed to follow a balanced hypocaloric diet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 29 publications
5
100
1
14
Order By: Relevance
“…No signifi cant differences were noted in the AI and RF measurements for coconut oil versus the control and SPM groups, suggesting no risk for an unusual blend of short and medium chain fatty acids content in coconut oil 21 . It was reported that supplementation with coconut oil did not cause dyslipidemia 23 , and was not a predictor for CHD in a food culture study 19 . The antioxidant properties of virgin coconut oil due to phenolic compounds has been reported 22 , but it is recommended not be used on a regular basis in adults.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…No signifi cant differences were noted in the AI and RF measurements for coconut oil versus the control and SPM groups, suggesting no risk for an unusual blend of short and medium chain fatty acids content in coconut oil 21 . It was reported that supplementation with coconut oil did not cause dyslipidemia 23 , and was not a predictor for CHD in a food culture study 19 . The antioxidant properties of virgin coconut oil due to phenolic compounds has been reported 22 , but it is recommended not be used on a regular basis in adults.…”
Section: Discussionmentioning
confidence: 94%
“…It is generally believed to be better than partially hydrogenated trans fats, and possibly animal fats, and contains an unusual blend of short and medium chain fatty acids 21 , antioxidant properties due to phenolic compounds 22 . It appears that its dietetic supplementation does not cause dyslipidemia and seems to promote a reduction in abdominal obesity 23 .…”
mentioning
confidence: 98%
“…abdominal no grupo que utilizou óleo de coco 144 . Apesar dos potenciais benefícios do óleo de coco no HDL, os estudos experimentais comprovam o efeito hipercolesterolêmico do coco e seus subprodutos, como o recente estudo com cobaias que comparou óleo de coco com azeite de oliva e óleo de girassol.…”
Section: Diretriz Brasileira De Hipercolesterolemia Familiar (Hf)unclassified
“…Coconut oil is rich in myristic and palmitic acids and increases LDL and HDL cholesterol (Micha & Mozaffarian, 2010), the latter having been observed in current study. The negative effects of these fatty acids appear to be the cause of the increased prevalence of CVDs, according to studies conducted in Asia, where coconut oil comprises up to 80% of the fat consumed in some regions (Kumar, 1997;Assunção, Ferreira, Santos, Cabral, & Florêncio, 2009).…”
Section: Resultsmentioning
confidence: 99%